Coupling between microtubule sliding, plus-end growth and spindle length revealed by kinesin-8 depletion - Wang, Haifeng (2010)
Mitotic spindle length control requires coordination between microtubule (MT) dynamics and motor-generated forces. To investigate how MT plus-end polymerization contributes to spindle length in Drosophila embryos, we studied the dynamics of the MT plus-end depolymerase, kinesin-8, and the effects of kinesin-8 inhibition using mutants and antibody microinjection. As expected, kinesin-8 was found to contribute to anaphase A. Furthermore, kinesin-8 depletion caused: (i) excessive polymerization of interpolar (ip) MT plus ends, which “overgrow” to penetrate distal half spindles; (ii) an increase in the poleward ipMT sliding rate that is coupled to MT plus-end polymerization; (iii) premature spindle elongation during metaphase/anaphase A; and (iv) an increase in the anaphase B spindle elongation rate which correlates linearly with the MT sliding rate. This is best explained by a revised “ipMT sliding/minus-end depolymerization” model for spindle length control which incorporates a coupling between ipMT plus end dynamics and the outward ipMT sliding that drives poleward flux and spindle elongation.